Low-Speed Oblique Impact Response of Adhesively Bonded Dissimilar Single-Lap Joints - Atahan, M. Gokhan; Apalak, M. Kemal (ASCE-Amer Soc Civil Engineers, 2022)
Adhesively bonded joints are widely preferred for joining similar and dissimilar materials due to the mechanical advantages they provide. As the demand for the adhesively bonded method increases, it is necessary to determine the behavior of joints under impact loads for joint design. The aim of this study was to investigate the low-speed oblique impact behavior of dissimilar single-lap joints and the effect of plastic deformation ability and strength of the adherends [(Top) Al 2024-T3-(Bottom) Al 5754-0, (Top) Al 5754-0-(Bottom) Al 2024-T3], overlap lengths (25, 40 mm), and impact energy (3, 11 J) on adhesive damage. The behavior of the joints determined by the numerical model under low-speed oblique impact was compared with experimental results. Considering the contact force-time, contact force-displacement, and adhesive damage, the numerical model was reasonably compatible with the experimental results. The damage initiation and propagation in the adhesive layer were determined by three-dimensional explicit finite-element analysis. In order to obtain suitability for the damage mechanism by observing the experimental bonding damage surfaces, the adhesive region was divided into three zones, the upper and lower adhesive interfaces and a middle adhesive layer between them. The different strength and plastic deformation ability of the adherends had a significant effect on the adhesive damage initiation and propagation. In the case of high strength and low deformation ability of the adherend material (Al 2024-T3) contacting with the impactor, a reduction of the adhesive damage occurred due to the deformation of the adherend material (bottom adherend) with low strength and high deformation capability. The oblique impact load and the different mechanical properties of the adherends greatly affected the adhesive damage initiation and propagation of single-lap joints.
Apalak, Mustafa Kemal/0000-0002-3263-5735; Atahan, Mithat Gokhan/0000-0002-8180-5876;
Keywords: Low Speed Impact; Oblique Impact; Single-Lap Joint; Cohesive Zone Model; Adhesive Failure; Dissimilar Joint